2018
DOI: 10.1002/hbm.24071
|View full text |Cite
|
Sign up to set email alerts
|

Network‐based decoupling of local gyrification in obsessive‐compulsive disorder

Abstract: Gyrification is associated with cortical maturation and closely linked to neurodevelopmental processes. Obsessive-compulsive disorder has previously been associated with neurodevelopmental risk factors. Using graph theoretical modeling we examined structural covariance patterns to assess potential disruptions in processes associated with neurodevelopment in OCD. In total 97 patients and 92 healthy controls underwent magnetic resonance imaging. Structural covariance networks based on local gyrification indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…These functional alterations may represent a possible mechanism between parenting and later depression symptoms or disorders in adolescents (Callaghan et al, 2017). Similar structural network alterations, that is, decreased local efficiency/clustering and atypical modularity, including decreased modularity based on the modularity index Q, have been demonstrated in adults with obsessive-compulsive disorder (Peng et al, 2014;Reess et al, 2018) and children with conduct disorder (Jiang et al, 2016). The observed network changes associated with parenting behaviors in the current study represent a potential framework for assessing the neurobiological mechanism which underlies the development of internalizing and externalizing problems in childhood and adolescence (Phua et al, 2019;Schwartz et al, 2016;Wu & Lee, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…These functional alterations may represent a possible mechanism between parenting and later depression symptoms or disorders in adolescents (Callaghan et al, 2017). Similar structural network alterations, that is, decreased local efficiency/clustering and atypical modularity, including decreased modularity based on the modularity index Q, have been demonstrated in adults with obsessive-compulsive disorder (Peng et al, 2014;Reess et al, 2018) and children with conduct disorder (Jiang et al, 2016). The observed network changes associated with parenting behaviors in the current study represent a potential framework for assessing the neurobiological mechanism which underlies the development of internalizing and externalizing problems in childhood and adolescence (Phua et al, 2019;Schwartz et al, 2016;Wu & Lee, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…Previous neuroimaging studies of global network metrics have reported more (Zhang et al, 2011(Zhang et al, , 2014, less (Shin et al, 2014;Armstrong et al, 2016;Jung et al, 2017;Reess et al, 2018a), or similar levels (Reess et al, 2016) of segregated organization of white matter-based structural connectivity networks, resting state functional connectivity networks, or local gyrification index-based structural covariance networks in individuals with OCD, compared to healthy controls. These inconsistent findings raise the need for larger-scale meta-analysis.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, a recent mega-analysis found higher covariance between volumes of left putamen and left frontal operculum, and higher covariance between volumes of right amygdala and ventromedial prefrontal cortex in OCD compared to healthy controls (Subira et al, 2016). Further, local cortical gyrification (associated with cortical maturation)based structural covariance network demonstrated lower covariance among mainly ventral brain regions in OCD compared to healthy controls (Reess et al, 2018b). However, few studies have explored intra-individual brain structural covariance networks in OCD; consequently our understanding of the factors that influence changes in global and regional network characteristics within individuals with OCD is limited.…”
Section: Introductionmentioning
confidence: 92%
“…The topological properties of SCNs including global and regional covariance parameters could be explored accordingly [ 22 ]. The graph theoretical network analysis of SCNs has been widely used in neurodegenerative diseases (e.g., Parkinson disease [ 23 , 24 ] and Alzheimer disease [ 25 ]) and psychological diseases (e.g., obsessive-compulsive disorder [ 26 , 27 ], schizophrenia [ 28 ] and major depression [ 29 ]). The brain morphometric and topological properties in these diseases were found rearranged, providing a fundamental for further improvement of clinical diagnose and specific treatments.…”
Section: Introductionmentioning
confidence: 99%
“…How the human brain reacts to the disconnection of motor efferent and sensory afferent after SCI has been attracting more and more attention. Graph theoretical network analysis has been applied in resting-state functional MRI (rs-fMRI) [ 26 , 27 ] and electroencephalography (EEG) studies [ 30 ] in SCI patients. However, to our knowledge, previous studies more focused on functional network changes [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%